Recent large-scale philophthalmosis outbreak in Portugal: inefficacy of common antihelminthic agents - Heneberg, Petr; Casero, María (Parasites & vectors, 2022)
BACKGROUND: Parasitic conjunctivitis caused by Philophthalmus spp. is a common ophthalmic disease in birds, with localized outbreaks occurring worldwide. There is no consensus on treating this disease; mechanical removal is considered a standard recommendation, but is associated with disease relapses within days or weeks. METHODS: From 2015 to 2020, we examined 4295 Larus michahellis and Larus fuscus gulls in southern Portugal for the presence of Philophthalmus spp. Due to the need to treat dozens of infected gulls in the rescue station, we tested three treatment regimens aimed at targeting Philophthalmus lucipetus in the infected gulls: (I) the ophthalmic application of levamisole; (II) the oral application of milbemycin in combination with praziquantel; and (III) the subcutaneous application of ivermectin. RESULTS: The outbreak of philophthalmosis in gulls in southern Portugal has been ongoing since the first cases were reported in 2015-2016. The prevalence of philophthalmosis has fluctuated annually, peaking a maximum of 10.3% in L. fuscus in 2017 and at 2.1% in L. michahellis in 2016. The infection intensity peaked at a median of 11.5 eye-flukes per host bird in L. fuscus in 2016 and a median of six eye-flukes per host bird in L. michahellis in 2017. Nine gulls were infected with >50 eye-flukes. None of the treatment options were effective at treating P. lucipetus infections: the numbers of eye-flukes in the infected birds did not decrease, and the clinical signs of the disease did not change. CONCLUSIONS: An outbreak of philophthalmosis in southern Portugal has massively affected two species of gulls in the region. Two previously suggested philophthalmosis treatments (ocular levamisole and praziquantel given orally), as well as a third mode of treatment with a previously failed compound (ivermectin administered subcutaneously) were used. However, the treatments did not affect the numbers of P. lucipetus in the eyes of the treated gulls. Further research should address ophthalmic gel formulations or sub-conjunctival delivery mode for antihelminthic drugs that are effective against Philophthalmus spp. in vitro.
Keywords: levamisol; praziquantel; Praziquantel; ivermektin; Helminth; infekce červy třídy Trematoda; Levamisole; Avermectin; Anthelmintics; Imidazothiazole; ptáci; Birds; Animals; Macrocyclic lactone; Digenea; Ivermectin; anthelmintika; zvířata; Population dynamics; Trematoda; epidemický výskyt choroby; Charadriiformes; Portugal; Philophthalmus lucipetus; Freshwater snail; Trematode Infections; Disease Outbreaks; Portugalsko; Conjunctivitis